Effects of chronic intranasal oxytocin on behavior and cerebral glucose uptake in juvenile titi monkeys. (March 2020) - Arias del Razo, Rocío; Berger, Trish; Conley, Alan J.; Freeman, Sara M.; Goetze, Leana R.; Jacob, Suma; Lawrence, Rebecca H.; Mendoza, Sally P.; Rothwell, Emily S.; Savidge, Logan E.; Solomon, Marjorie; Weinstein, Tamara A.R.; et al.
Highlights: Chronic use of IN OXT represents a closer approach to its intended use as a life-long treatment for social deficits in ASD. Animals treated with IN OXT showed a moderate increase in social behavior during treatment. We found important sex differences in the direction of social behaviors when given the choice between parents and strangers. IN OXT increased brain activity across the social salience network as a whole after one month of daily treatment. OXT-treated males displayed more anxiety-like behavior during an anxiety test, no significant effects were found in females. Abstract: Intranasal oxytocin (IN OXT) has been proposed as a treatment for autism spectrum disorder (ASD); however, little is known about the effects of long-term exposure. This is the first study in a non-human primate species to examine how developmental exposure to chronic IN OXT affects juvenile's interactions with family members, social preference for parents versus strangers, anxiety-like behavior, and cerebral glucose metabolism. Titi monkeys are socially monogamous and biparental; their family bonds share important characteristics with human family bonds. Fourteen males and 15 females were treated intranasally with saline (n = 14) or 0.8 IU/kg OXT (n = 15), daily from 12 to 18 months of age. Compared to SAL-treated animals, OXT-treated animals of both sexes spent significantly more time grooming other family members (F1  = 8.97, p = 0.006). Overall, OXT-treated subjects were more social (F1  = 8.35, p = 0.005) during preference tests. OXT-treated females displayed an enhanced preference for their parents (t = 2.265, p = 0.026). OXT-treated males had a blunted preference for their parents and an increase in the time spent near unfamiliar pairs (F1 = 10.89, p = 0.001). During anxiety tests, OXT-treated males refused to complete the task more often than SAL-treated males and had longer latencies (p < 0.0001). Neuroimaging studies revealed that OXT-treated animals had higher glucose uptake across the social salience network as a whole after one month of treatment (F1, 9 = 1.07, p = 0.042). Our results suggest moderate prosocial effects of chronic IN OXT, that did not depend on anxiolytic properties. We also found important sex differences that should be considered in a translational context.